(untitled) (Scientific journal of the Fergana State University, 2025)
In modern society, changes in human values and moral standards have accelerated and become more complex processes in recent decades. This article analyzes the change in human values and moral standards in the context of time, their role and impact on society. Considering the historical development of the concept of human value and its modern form, the article emphasizes the variability of values such as human rights, equality, justice and others. The article highlights the impact of globalization, technological progress and social networks on human value and moral standards. It also explores how ethics and moral values take new forms in the social system, legislation and education. In addition, the article discusses contemporary moral issues such as the development of artificial intelligence, environmental issues and ethical dilemmas in social networks. The relationship between moral norms and human values reveals the role they play in ensuring social justice, sustainable development and protection of individual rights in society. The influence of education and culture on human moral norms and values is also considered, and the formation of new moral norms and public attitudes towards them is also discussed. The article emphasizes that the integration of moral values and the concept of human value in modern society is necessary to ensure sustainable social development and a just society.